2001
DOI: 10.1039/b104161b
|View full text |Cite
|
Sign up to set email alerts
|

Novel octahedral tungsten sulfidocyanide cluster anion [W6S8(CN)6]6–

Abstract: Novel tungsten octahedral sulfidocyanide cluster compounds Na6[W6S8(CN)6].18DMSO 1 and K6[W6S8(CN)6] 2 have been synthesized and characterized by X-ray crystallography and NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Each rhenium atom is coordinated to one cyano group forming an almost linear ReϪCϪN fragment. Selected bond distances of structures 1, 2 and other related complexes are listed in Table 1 6 ] we can say that the oxidation does not significantly affect these distances (within the limits of the errors obtained). www.eurjic.org Figure 2.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Each rhenium atom is coordinated to one cyano group forming an almost linear ReϪCϪN fragment. Selected bond distances of structures 1, 2 and other related complexes are listed in Table 1 6 ] we can say that the oxidation does not significantly affect these distances (within the limits of the errors obtained). www.eurjic.org Figure 2.…”
Section: Resultsmentioning
confidence: 95%
“…Chemical analysis (EDAX) of the crystals showed that they contained no potassium. The magnetic susceptibility of 1 is µ eff (298) ϭ 1.81 µ B which corresponds to one unpaired electron per formula unit [La(H 2 O) 3 6 ] 3ϱ . Structure 1 contains one rhenium atom (Re1), two tellurium atoms (Te1, Te2), one cyano group (C1, N1), Ln1, and O1 (coordinated water) in its asymmetric unit ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations